Free-floating and spinning thrombus of the basilar artery: A case report. Issue 21 (28th May 2021) - Kim, Keon-Yeup; Lee, Sang-Hun
Abstract: Rationale: Free-floating thrombi in the intracranial artery are rare. We report a case of a free-floating and spinning thrombus caused by turbulent flow distal to the basilar artery stenosis. We compare thrombus changes in a series of images according to time and describe the approach to treatment and thrombosis resolution. Patient concerns: A 55-year-old man presented to the emergency department on March 21, 2020, with left-sided weakness, bilateral limb ataxia, and a one-day history of dysarthria. Brain magnetic resonance imaging showed multifocal infarctions in the pons and cerebellum with severe basilar stenosis. Diagnoses: Digital subtraction angiography showed severe focal stenosis. A relatively large oval-shaped mobile thrombus was observed spinning due to turbulent flow at the distal portion of the stenosis. Interventions: We administered a combination antithrombotic regimen of warfarin and clopidogrel for 50 days. Outcomes: No thrombus was observed on the third follow-up digital subtraction angiography. Lessons: No previous study has directly observed a mobile thrombus in the intracranial artery using digital subtraction angiography. We used a combination antithrombotic strategy, which was effective after long-term, rather than short-term, use.